Food as a Sustainable Alternative Tourism Promotion in 3S Destinations - BABOLIAN HENDIJANI, Roozbeh (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Purpose - The tourism sector has played an important role for the economy of island destinations such as Bali. The importance of food tourism as an alternative tourism to promote sustainability for Bali has not been fully explored in terms of visitors’ point-of-view; therefore, the knowledge about satisfaction of tourists about food experience is still in its initial stages. This research aims to explore the satisfaction of international tourists and asses if food has the potential to be used as an alternative to promote sustainable tourism. Design – Besides the theoretical implication of this research regarding tourism industry in Indonesia, this study also gives practical application into the matter of tourism industry in Indonesia. Methodology - This research applied a quantitative method where self-administrated questionnaires were distributed among 150 participants. Some statistical analysis such as factor analysis, multiple linear regression and descriptive analysis were used to analyze the data. Findings - The finding of analysis showed that “environment” and “serving” were significant factors that affected the satisfaction of tourists. The findings have implications for food tourism management and marketing strategies in order to promote sustainable tourism in 3s destinations. Originality - This study was one of the few to assess the role of food as an alternative tourism in 3S destination.